Detection of immunoregulator molecules inside non-functional kidney allografts upon a rejection episode - Naka, Erika Lamkowski (2008)
Introduction: Tim-3 is a Th1 lymphocytes membrane protein with inhibitory function. Its ligand, the galectin-9, was recently identified, and it is expressed in some lymphocytes population. In addition, endothelial cells and fibroblasts can also express the galectin-9, according to the local cytokine milieu. These molecules, together with the CD4+CD25+ T lymphocytes, act as important regulatory tools to the immune system. FOXP3 is a transcription factor associated to the regulatory CD4+CD25+ T cells. Purpose: To assess the expression of these immunoregulator molecules inside kidney allografts during acute rejection episodes. Methods: By using a quantitative polymerase chain reaction assay, we measured the levels of the RNA messenger for Galectin-9, Tim-3 and FOXP3, in 24 sampling attained from allograft nephrectomy for acute nonvascular rejection (n=5), acute vascular rejection (n=14) or loss due to a nonimmune cause (n=5, as control). The granzyme B molecules, perforin and interferon-gamma were also analyzed, since they represent host-driven immune response. Results: Median mRNA levels of all immunoregulator as well as cytolytic molecules correlated to the severity of the rejection: p=0.024 for galectin-9, p=0.008 for Tim3, p=0.005 for FOXP3, p=0.008 for perforin and interferon-gamma; and p=0.003 for granzim B. Conclusion: Among all the studied molecules, mRNA levels were higher inside allografts which presented more severe rejection. This data suggest the immune response is a dynamic process, and it involves both cytopathic and regulatory mechanisms. The acute rejection episode could be consequence of a disproportion in such response.